Bank Efficiency and Stability in ASEAN-5: A DEA Window Analysis - Desmy Riani; Ofan Maulana Yudista; Fitria Ika Septiyani (Universitas Pendidikan Ganesha, 2026)
This study evaluates the efficiency and intertemporal stability of listed banks in the five largest ASEAN economies using data envelopment analysis window analysis. The sample comprises 36 banks from Indonesia, Malaysia, the Philippines, Singapore, and Thailand, generating 360 bank-year observations from 2014 to 2023. An output-oriented variable-returns-to-scale model was applied using total assets, labor costs, and third-party funds as inputs and total loans and total income as outputs. Efficiency stability was assessed using long-distance-per-year, long-distance-per-window, long-distance-per-period, and standard-deviation indicators. The results show that the banks achieved an average efficiency score of 84.2% during the observation period. Singapore recorded the highest country-level efficiency, while Malaysia exhibited the greatest efficiency stability. At the bank level, DBS Group Holdings achieved the highest average efficiency, whereas CIMB Group Holdings recorded the most stable performance. The results also identify substantial opportunities to improve credit disbursement and income generation through more effective management of assets, labor costs, and third-party funds. This study extends cross-country banking-efficiency research by combining dynamic efficiency measurement with intertemporal stability analysis and offers practical benchmarks for strengthening resource allocation and operational resilience in ASEAN banks.